Performance comparison between the conventional and blade-designed two-fluid pressure nozzles via CFD simulation - Che-Hao Hsu; Hong-Ping Cheng; Yu-Cheng Chou; Guang-Xiang Liu; Hsu-Yu Chen; Chien-Hsun Lee; Chin-Chi Cheng (Heliyon)
This study aims to evaluate the performance differences between a conventional pressure twin-fluid nozzle and a blade-designed nozzle, hypothesizing that the blade-designed nozzle can achieve superior gas-liquid interaction. The research of the velocity distribution and atomization behavior of two nozzle designs provides insights into improving nozzle efficiency and suitability for various industrial spray applications. Simulations were conducted under fixed pressure (2 bar) using two Newtonian liquids—water and a glycerol/water mixture with viscosities of 1 mPa s and 100 mPa s, respectively—and air velocities of 60 m/s and 100 m/s. Results demonstrate that the blade-designed nozzle's dispersed-blade outlet effectively directs internal gas flow, reducing velocity stratification and enhancing gas-liquid interaction near the nozzle exit. This design results in a broader atomization range and more uniform velocity distribution, making it suitable for industrial applications requiring efficient and consistent spray coverage.